2019
DOI: 10.1007/jhep06(2019)044
|View full text |Cite
|
Sign up to set email alerts
|

AdS3 four-point functions from $$ \frac{1}{8} $$-BPS states

Abstract: We compute four-point functions in the Heavy-Heavy-Light-Light limit involving a large family of 1 8-BPS heavy states whose dual supergravity solutions are explicitly known, avoiding the use of Witten diagrams. This is achieved by using the AdS/CFT dictionary of type IIB supergravity on AdS 3 × S 3 × M 4 that maps supersymmetric heavy operators whose conformal dimension is the order of the central charge to explicit asymptotically AdS supergravity solutions. Using the Ward Identities for the generators of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
(139 reference statements)
0
33
0
Order By: Relevance
“…N b /N is a free parameter and so following [14,15], we can take a perturbative approach and extract the eikonal order by order in N b /N . Such an approach is well-adapted for the calculation of the HHLL correlators 1 and several explicit examples are known [29][30][31][32][33]. We study the OPE decomposition of such correlators in the channel describing the fusion of a heavy and light state, producing an intermediate excited heavy state -this we call the "cross channel".…”
Section: Jhep11(2020)018mentioning
confidence: 99%
See 2 more Smart Citations
“…N b /N is a free parameter and so following [14,15], we can take a perturbative approach and extract the eikonal order by order in N b /N . Such an approach is well-adapted for the calculation of the HHLL correlators 1 and several explicit examples are known [29][30][31][32][33]. We study the OPE decomposition of such correlators in the channel describing the fusion of a heavy and light state, producing an intermediate excited heavy state -this we call the "cross channel".…”
Section: Jhep11(2020)018mentioning
confidence: 99%
“…The LLLL version of this correlator was derived in [40] and it will be analysed in section 4.3. 6 Here we follow the conventions of [30,32].…”
Section: The Cft Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As briefly mentioned in the previous section, some investigation on the holography of the microstate geometries have been conducted; for example, a set of nice computations of 4-point functions involving the two heavy operators dual to the geometry and two light operators dual to supergravity mode on top on that geometry were computed [44,52,[55][56][57][58][59]. We will now focus on the results of [20], since there the computation on the geometry (2.15) was put forward.…”
Section: Holographic Interpretationmentioning
confidence: 99%
“…i.e. superstrata, two-point function was studied in [83,87,88]. Most of these works focused on the shallow limit but, in [89], the deep throat limit of the (1, 0, n) superstratum was studied using a WKB technique, and it was found that two-point functions decay as in the BTZ black hole for t √ N 1 N 5 R y , while for t ∼ N 1 N 5 R y large echoes are coming back from the cap.…”
Section: Precision Holographymentioning
confidence: 99%